Protection of external borders of the Schengen area - Bugisová, Zuzana (2017)
In the light of recent migration crisis and terrorist events, European states moved the security of state to the highest priority. The most effective way how to protect the state from illegal migrants, terrorists, traffickers or other outside threats is to secure and control state borders. In Schengen Area is controlling of external common border especially important because of the abolishment of internal borders and thus the possibility of free movement of people throughout the whole Schengen territory. Controlling and management of actual physical borders of Schengen is extremely important, but could be also very difficult, if all the people wanting to enter its territory would suddenly gather on its border. Therefore nowadays developed European countries mainly rely on extraterritorial migration control systems, which are tasked to reveal the amount of individuals who want to enter Schengen territory sooner than these people actually reach the Schengen border but also are ought to distinguish between desired and undesired migrant and take proper action in order to protect Schengen external border. The aim of this paper is to characterize actions and practices of different actors located within and outside of the Schengen Area that contribute to the protection and control of Schengen external border extraterritorially. This characterization stands on the Principal-Agent theory, which is based on delegation of tasks and responsibilities from one actor – principal to the other – agent. Another aim closely connected with these actions is their analysis using the SWOT approach in order to find out what are internal and external inhibitors and enhancers that can help or hinder the ability of the agent to sufficiently protect Schengen external borders. Actors analyzed are Schengen Member States, the European Union, transit countries in the Schengen neighborhood and private carrier agencies.